The doctoral path in urban studies in Italy: between personal expectations and institutional goals - Grazia Di Giovanni; Cora Fontana (Italian Journal of Planning Practice, 2016)
In the hybrid working contemporary landscape, the purpose of a doctoral programme should be the scientific and methodological training of multi-skilled and versatile researchers, not strictly orienting the students toward a specific academic or not academic career. This assumption seems particularly relevant for Ph.D. programmes focused on cities. In order to corroborate this thesis and to understand the opinions among Ph.D. candidates in Italy, a direct survey among doctoral students in urban studies (and interrelated branches of knowledge such as planning, urban geography and sociology) has been conducted. The survey investigates the differences and similarities between personal expectations and institutional goals, and what is the general approach of Ph.D. schools in Italy. The results show an enduring predominant interest of Ph.D. students towards academic careers, even if a shift can be observed in how Ph.D. education is perceived.